ANALISA PERBANDINGAN JENIS BAHAN BAKAR DENGAN NILAI RON 92 DARI BERBAGAI PABRIKAN TERHADAP DAYA, TORSI, DAN EMISI GAS BUANG PADA MOTOR BENSIN 150CC: THE COMPARISON ANALYSIS OF FUEL TYPES WITH RON 92 VALUE FROM VARIOUS MANUFACTURERS ON POWER, TORQUE, AND EXHAUST EMISSIONS IN 150CC GASOLINE MOTOR - Bima, Harvei Bima Kusuma Putra (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2022)
Gasoline is a type of oil-based fuel commonly used in motor vehicles. The quality of gasoline can be determined by its octane rating, which determines the efficiency of the combustion process. This research aims to investigate the differences in power, torque, and exhaust gas emissions when using RON 92 gasoline from Pertamax, Shell Super, and BP92. The data processing in this study utilized factorial design of experiments (DOE) to analyze the effects and differences. Based on the research findings, it can be concluded that there are significant differences in power, torque, and exhaust gas emissions among the tested RON 92 gasoline fuels in a 150cc gasoline engine. BP92 demonstrated the best performance with a maximum power of 14.4 HP at 9000 RPM, maximum torque of 11.34 Nm at 9000 RPM, and lower emissions of CO, HC, and CO2 compared to Pertamax and Shell Super at certain RPM levels. This indicates that the use of BP92 provides better value in improving the performance of a 150cc gasoline engine and reducing exhaust gas emissions.